Retrograde Approach for Percutaneous Ventricular Septal Defect Closure: Is It Really Better Than Antegrade? - Yashchuk, Nataliia S.; Ditkivskyy, Igor O.; Soi, Alisa P.; Cherpak, Bogdan V.; Borodinova, Olha S.; Yermolovych, Yuliia V. (Ukrainian Journal of Cardiovascular Surgery, 2025)
Introduction. This study was designed to compare the antegrade and retrograde approaches for percutaneous ventricular septal defect (VSD) closure, in light of ongoing debates regarding the advantages and disadvantages of each approach. To the best of our knowledge, there is currently no published literature comparing the immediate and longterm outcomes of these two techniques for transcatheter VSD closure. Materials and methods. From August 2012 to January 2025, 254 patients underwent percutaneous ventricular septal defect closure using various devices. Of these, 103 patients were treated with the antegrade approach (Group 1), and 151 patients with the retrograde approach (Group 2). The mean follow-up period was 59.5 ± 35.5 months in Group 1 and 54.5 ± 21.4 months in Group 2 (p = 0.45). Results. The procedure was successful in 97 patients (94.17%) in Group 1 and in 151 patients (100%) in Group 2. The number of major complications was approximately equal in both groups (p = 0.49). Two patients in Group 1 were referred to surgery due to the new onset of significant aortic or tricuspid insufficiency. One patient in Group 2 developed complete atrioventricular (A-V) block complicated by dilated cardiomyopathy two years after perimembranous ventricular septal defect closure. Four patients (3.88%) in Group 1 experienced hemodynamic collapse due to valve compromise from the arterio-venous loop, compared to zero patients in Group 2 (p = 0.014). The number of minor complications was similar in both groups (16 patients, 15.53%, in Group 1 vs 17 patients, 11.25%, in Group 2; p = 0.31). The mean fluoroscopy time and mean procedure time were significantly lower in Group 2 compared to Group 1 (31.56 ± 23.7 vs 17.6 ± 16.2 minutes, p = 0.001; and 55.8 ± 32.9 vs 117.5 ± 57.8 minutes, p < 0.001). Conclusions. The retrograde approach appeared to be technically simpler, requiring only one vessel puncture, and had zero complications associated with the creation of a transcardiac loop. The number of perioperative, medium-term, and long-term complications was similar in both groups. However, the antegrade approach can still be applied in patients with low weight and large defects, as well as in cases with a deficient rim to the aortic valve or defects requiring the implantation of asymmetric devices.